The Shifting Context of Special Education Teachers' Work. (June 2023) - Gilmour, Allison F.; Nguyen, Tuan D.; Redding, Christopher; Bettini, Elizabeth
We used five waves of nationally representative data over 16 years from the Schools and Staffing Survey, National Teacher Principal Survey, and Teacher Follow-up Survey to descriptively examine how the roles, responsibilities, preparation, and supports for special educators have changed over time. We then used regression to investigate how these variables were associated with special educator attrition. This information is essential to ensure teacher education adequately prepares special educators for the contexts in which they work. We identified some changes in special educators' work environment, including substantially increased use of team teaching. Our results indicated special educator attrition declined from 2000 to 2012, and this decline was primarily driven by reductions in movement between schools. Regression analysis provided little insight into the variables associated with this decline, suggesting a need for future research.